Occurrence, seasonal variation and risk evaluation of selected endocrine disrupting compounds and their transformation products in Jiulong river and estuary, China. (August 2019) - Ashfaq, Muhammad; Sun, Qian; Ma, Cong; Rashid, Azhar; Li, Yan; Mulla, Sikandar I.; Yu, Chang-Ping
Abstract: In the present study, 13 endocrine disrupting compounds (EDCs) and their transformation products (TPs) were monitored in Jiulong River and its estuary, China in different seasons. The analytes included antimicrobials [triclosan (TCS) and triclocarbon (TCC)]; estrogens [estrone (E1), estradiol (E2), estriol (E3) and ethinylestradiol (EE2)]; alkylphenol ethoxylates [4-n-nonylphenol (NP) and 4-n-octylphenol (OP)] and the TPs [methyl triclosan (MeTCS), carbanilide (NCC), dichlorocarbanilide, 4-hydroxy estrone (4-OH E1) and 4-hydroxy estradiol (4-OH E2)]. A significant seasonal variation was observed for most EDCs. Approximately, 79% of the total E2 residues were detected in the normal season in comparison with the wet season to indicate recalcitrant behavior of E2 during the normal season. Risk assessment revealed that E2 was most potent among the EDCs to cause highest risk to both vertebrate and invertebrate aquatic species, whereas, E1, EE2, MeTCS and TCS also showed relatively high risk for some surface water aquatic species. Graphical abstract: Unlabelled Image Highlights: 13 endocrine disrupting compounds were investigated in Jiulong river & estuary. The occurrence and detection frequency of the antimicrobials was highest. Significant seasonal variation was observed for most of the compounds. Estradiol (E2) was most potent among these compounds to cause highest risk.